2015
DOI: 10.7150/ijms.12032
|View full text |Cite
|
Sign up to set email alerts
|

Secondhand Smoke Exposure Reduced the Compensatory Effects of IGF-I Growth Signaling in the Aging Rat Hearts

Abstract: Background: Secondhand smoke (SHS) exposure is associated with increased risk of cardiovascular disease. Aging is a physiological process that involves progressive impairment of normal heart functions due to increased vulnerability to damage. This study examines secondhand smoke exposure in aging rats to determine the age-related death-survival balance.Methods: Rats were placed into a SHS exposure chamber and exposed to smog. Old age male Sprague-Dawley rats were exposed to 10 cigarettes for 30 min, day and ni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 34 publications
1
8
0
Order By: Relevance
“…Similar results were observed with secondhand smoke or lipopolysaccharide (LPS) treatment. Secondhand smoke or LPS induce more cardiac dysfunction, fibrosis, inflammation, and oxidative stress in aged mice than in young mice [ 36 , 37 ]. Aging-associated cardiac abnormalities are manifested as diastolic cardiac dysfunction, cardiac hypertrophy, and fibrosis, as well as impaired contractile function [ 38 , 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Similar results were observed with secondhand smoke or lipopolysaccharide (LPS) treatment. Secondhand smoke or LPS induce more cardiac dysfunction, fibrosis, inflammation, and oxidative stress in aged mice than in young mice [ 36 , 37 ]. Aging-associated cardiac abnormalities are manifested as diastolic cardiac dysfunction, cardiac hypertrophy, and fibrosis, as well as impaired contractile function [ 38 , 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Phosphorylation was unchanged in 14-month-old mice [ 82 ] or 20‒24-month-old rats [ 83 ], and p-STAT3beta was not altered in 24-month-old mice [ 84 ] ( Table 5 ). Three studies showed that the level of STAT3 expression was increased in response to aging in old mice [ 82 ], hamsters [ 72 ] and rats [ 73 ]; however, these findings are limited since the activation (i.e., phosphorylation) was not examined.…”
Section: Effect Of Cardiovascular Risk Factors On Cardiac Stat3 Unmentioning
confidence: 99%
“…Both active and passive (secondhand) smoking are predominant risk factors for coronary heart disease [ 86 ]. We et al reported that passive smoking increases cardiac STAT3 expression in young rats [ 73 ], but does not alter STAT3 expression in hamsters [ 72 ] ( Table 4 ). In aged rats and hamsters exposed to passive smoking, cardiac STAT3 expression showed a tendency to increase [ 72 , 73 ].…”
Section: Effect Of Cardiovascular Risk Factors On Cardiac Stat3 Unmentioning
confidence: 99%
“…Previous studies have shown that exposure to ETS will reduce the cardiomyocyte survival rate and accelerate age-related cardiac disease in aging animals [11, 22]. However, cell death and cell apoptosis can not be detected in the ETS exposure group comprising C57BL mice hearts (Figure 1).…”
Section: Discussionmentioning
confidence: 85%
“…The GYTS discovered that deaths that were caused by smoking were twice the number of those who started to smoke before the age of eighteen [8, 9, 10]. In our previous study, we discovered that ETS exposure accelerated age-related cardiac disease and reduced the IGF-1 growth signaling in aging rat hearts [11, 12]. Furthermore, ETS exposure can disturb the oxidative processes in myocardial mitochondria and lead to cardiomyopathy [13].…”
Section: Introductionmentioning
confidence: 99%